Small pilot study of ultra-high pressure reverse osmosis technology for treating landfill leachate in Northwest China - ZHANG Huixiang; ZHANG Xuemin; SUN Sanxiang; LI Li (Gongye shui chuli)
Landfill leachate has high COD, ammonia nitrogen and conductivity, these complex pollution characteristics make the reverse osmosis treatment load too high, which further leads to the decrease of membrane performance and membrane permeate flux. This paper took influent pH, operating pressure and temperature as influencing factors, and COD, ammonia nitrogen and conductivity of concentrate and produced water as evaluation parameters, to derive the optimal working conditions by analyzing the changes of concentration multiplication rate, membrane flux and water production rate to treat leachate from a landfill plant in Lanzhou. The results showed that the effect of the three factors on the DTRO system was operating pressure>temperature>inlet pH, and when the pH was 6.5, the operating pressure was 6 MPa, and the temperature was 40 ℃. The system had the highest concentration multiplier of 4.07 and the best water production rate of 75.6% consistently, which reduced the load for subsequent concentrate treatment.